Interview with Rotsay Rosales Valladares: rethinking Civic Education in Costa Rica - López López, Maximiliano (2021)
In this interview Dr. Rotsay Rosales Valladares talks about current Civic Education, which, in his opinion, explains the passivity and resignation that is transmitted to young people. Dr. Rosales Civic Education reinforces the promotion of docile and uncritical consumers, instead combating the economic model of global capitalism with critical citizens with high civic commitment, that’s Why Dr. Rosales Valladares, proposes an axiological proposal, in order to Civic Education that contributes to the transition from this post-democratic liberal society to a post-liberal democratic society and country.